Evaluasi Pelaksanaan Dan Sikap Pembudidaya Ikan Terhadap Program Dana Desa Pada Budidaya Ikan Lele Di Desa Lawang Agung Kecamatan Air Periukan Kabupaten Seluma - Amin Akbar; Herri Fariadi; Evi Andriani (University of Prof. Dr. Hazairin, SH, 2026)
A positive attitude of fish farmers is crucial in the management of village funds to ensure that the objectives of fund allocation are achieved. Therefore, an evaluation of the implementation of the Village Fund Program, including the distribution mechanisms and activity implementation, is necessary. This study aims to evaluate the implementation of the Village Fund Program and analyze the attitudes of fish farmers toward the program in catfish aquaculture in Lawang Agung Village, Air Periukan Subdistrict, Seluma Regency. The research method employed was descriptive quantitative analysis measured using a Likert scale. The results indicate that, normatively and administratively, the program implementation has been well conducted. This is evidenced by indicators showing that the village government has presented village financial reports in community meetings (73%), disclosed the use of village funds transparently (83.1%), and utilized village funds in accordance with the expectations of fish farmers (77.3%). Regarding attitudes toward the Village Fund Program, of the 62 respondents surveyed, 48 respondents (78%) showed a positive attitude, while 14 respondents (22%) exhibited a negative attitude. Thus, fish farmers support and perceive that the achievement of the Village Fund Program in Lawang Agung Village, Air Periukan Subdistrict, Seluma Regency has provided benefits to the community.